(untitled) (International Journal of Current Engineering and Technology, 2014)
To identify the bacteria and fungi from the otitis media inflammation samples taken during otitis media of patients with acute, This work was applied on 44 otitis media patients admitted to the Hospital in Hilla with age range (9-60) years . Swabs cultures of otitis media patients reveals major types of bacteria growth shown in Isolated and diagnostic types of bacteria G+ve and G-ve which form G-ve with persentige60.97% also M.catarhals form persentige21.9% and other of these Ps. aeroginosa form persentige20.7%and lessness famous H.influnza form persentige 1.21.%the bacteria G-ve form persentige 39.2% in front of St.pnemonia persentige form persentige19.5% and other bacteria S,aurius persentige 17.7% and lessness famous of bacteria St, pyogens in persentige 2.03%. This study also Isolated and diagnostic type of fungi compare to the patints of otitis which type of sample fungi 54 infront of A.flaves persentige 24.7% and other of it A.fumguts in persentige 22.2